КОГНІТИВНЕ МОДЕЛЮВАННЯ ВПЛИВУ ВЗАЄМОДІЇ ПОКАЗНИКІВ ПЛАНУВАННЯ ТА ВИКОНАННЯ БЮДЖЕТНОГО ПРОЦЕСУ ЗСУ НА ЕФЕКТИВНІСТЬ ОБОРОННОЇ РЕФОРМИ (International Journal of Innovative Technologies in Economy, 2018)
A significant part of the indicators of planning and implementation of the budgetary process of the Armed Forces of Ukraine (MAT) are interrelated, which affect the effectiveness of the budget policy of defense reform. Questions arise as to how to establish the properties and relationships of these links using methods of mathematical modeling.The cognitive model of the interaction of the indicators of planning and implementation of the budget process of the Armed Forces of Ukraine on the effectiveness of defense reform in Ukraine establishes the existence of links in the management of the effectiveness of defense reform, which can be defined as critical, that is, risk-averse and provides an opportunity to assess the risk level of each contour and to model scenarios and options for improving planning and budgeting for defense reform.